Penubuhan dan bidang kuasa Mahkamah Muamalat di Malaysia: Isu dan cabaran - Hassan, Rusni; Hussain, Mohammad Azam; Yusoff, Adnan (Dewan Bahasa dan Pustaka, 2013)
The Malaysian Financial Sector Master Plan 2001-2010 provides a blueprint for the establishment of a Syariah commercial court within the Malaysian judiciary system to address the legal issues related to Islamic finance.Accordingly, the Judicial Department has taken proactive steps to set up a special division under the civil courts to handle cases related to banking and finance.The establishment of specialized courts is pursuant to the Practice Direction No. 1/2003 issued by the Chief Justice (as he then was), Dato’ Haidar Mohd Nor. Since 2003, cases relating to Islamic finance have been registered at the High Court Commercial Division 4. This special court,known as the Muamalat Court, began operations in February 2009 at the Kuala Lumpur High Court. This paper discusses the establishment, structure and function of the Muamalat Court as well as highlighting the issues and challenges encountered by this court